ANALISIS KEBIJAKAN PENDIDIKAN KARAKTER DI INDONESIA - Nur Salsabila (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines the integration of the Strengthening Character Education (PPK), the Merdeka Curriculum, and the Pancasila Student Profile (P5) within school learning practices as part of efforts to enhance student character formation and learning autonomy. The research aims to describe how these three components operate together at the implementation level and to identify supporting and inhibiting factors within the school environment. Using a qualitative descriptive method, data were collected through observations, interviews, and documentation involving teachers, school leaders, and students. The findings indicate that the Merdeka Curriculum provides a flexible framework that allows PPK value (religiosity, nationalism, integrity, independence, and cooperation) to be embedded naturally into daily learning. Meanwhile, P5 acts as a practical guide that helps schools translate character values into real projects and activities. The analysis also shows that teacher readiness, availability of learning resources, and school culture significantly influence successful implementation. However, several challenges remain, including uneven teacher competence, varying levels of parental involvement, and limited infrastructure in some schools. Overall, this study concludes that integrating PPK, the Merdeka Curriculum, and P5 strengthens holistic character development and student competence when supported by professional teachers and a collaborative school ecosystem.